Deposition growth of Zr-based MOFs on cerium phenylphosphonate lamella towards enhanced thermal stability and fire safety of polycarbonate. (15th September 2020) - Sai, Ting; Ran, Shiya; Guo, Zhenghong; Yan, Hongqiang; Zhang, Yan; Song, Pingan; Zhang, Tao; Wang, Hao; Fang, Zhengping
Abstract: The fabrication of engineering plastics combining high efficiency flame retardancy and thermal resistance are essential for practical applications. A novel halogen-free binary hybrid with lamellar and porous structure, Zr-BDC@CeHPP, was created by hydrothermal reaction, thereafter blended with polycarbonate (PC) to improve its thermostability and fire safety. With 2 wt% Zr-BDC@CeHPP, temperatures under peak decomposition rates ( T max1 and T max2 ) of PC were increased by 28 and 34 °C under oxidizing atmosphere. Time to reach PHRR (t-PHRR) and time to ignition (TTI) and of PC were effectively prolonged to 145 and 18 s, respectively. In comparison with pure PC, the peak of heat release rate (PHRR), total heat release (THR), peak specific extinction area (PSEA) and total smoke release (TSR) of PC composites were reduced by 45%, 20%, 74% and 18%, respectively. Moreover, the flame retardant PC reached V-0 rating in UL-94 vertical burning test. The results indicated that the hybrid was able to fully utilize the advantages of Zr-BDC and CeHPP. In the ignition and middle periods of combustion, Zr-BDC@CeHPP played roles in delaying and suppressing explosive combustion. In severe combustion stage, Zr-BDC@CeHPP could catalyze the char-forming process and serve as a barrier. Graphical abstract: Image 1